THE ANALISYS OF READING NARRATIVE TEXT BY STUDENTS OF ENGLISH EDUCATION DEPARTMENT POTENSI UTAMA UNIVERSITY MEDAN - Yenita Uswar; Nova Andriani (Journal MELT (Medium for English Language Teaching), 2019)
Narrative text is one of the most frequent lessons in Education world especially English language education in Indonesia. Therefore, at least we should be able to understand narrative text very well therefore later when we read the stories in English, we are directly able to digest the story. And can apply it in teaching either at school or at the University. This main research is to determine how far English Language Education Students of Potensi Utama University understand the Genre in English especially about Narrative Text. This research is a Classroom Action Research (CAR) that will be carried out to determine the extent of students' ability to analyze Narrative Text. To achieve the desired goal, this CAR will be implemented in 3 cycles. Each cycle consists of 3 lecture meetings, namely the provision of material and text practice examples. At the end of the cycle a test was held to find out the ability and progress of students in analyzing Narrative text. Feedback is given from the test results to overcome the problems that arise in the previous cycle. The research subjects were the 4th semester students of the English Language Education Department of Potensi Utama University Medan, totaling 34 students. The objectives of the study are: a) to help overcome student problems in understanding reading text especially narrative text and improve the ability of students reading comprehension and b) to provide a basis learning models for reading English Language skills at university